Type of Feet in a Mexican Population: Analysis of the Footprint Morphology and Literature Review - Ramos-Frutos, Jorge Armando; Miguel-Andrés, Israel; León-Rodríguez, Miguel; Ortiz-Lango, Luis Angel; Orozco-Villaseñor, Sergio Luis; Vidal-Lesso, Agustín (Revista Mexicana de Ingenieria Biomedica, 2023)
There is no specific age when the vault of the feet is completely formed. The objective of this study was to analyze the footprint morphology and obtain the Chippaux-Smirak Index in a Mexican population to identify the type of feet and its prevalence. A database of images of the soles of both feet was analyzed. The database contained images of 1,014 persons between 2 and 73 years old from Guanajuato state, Mexico. Moreover, a literature review was performed to identify the type of feet in the Mexican population. It was observed that less than 17 % of the population have cavus foot (p= 0.018). Furthermore, less than 25 % of the population between 17 and 73 years have flatfoot 3 (p= 0.0079) in the left foot. Also, only nine articles related to the type of foot in the Mexican population were found, but most of them were performed on young population. The formation of the medial arc could be beyond the first decade of life and the relatively high prevalence of flatfoot in adult life should be studied. Finally, the results found can be useful for orthopedists, physiotherapists, clinicians, and parents who are concerned about the foot health of their children.